2019
DOI: 10.1055/s-0039-1693465
|View full text |Cite
|
Sign up to set email alerts
|

Simulation in Neonatal-Perinatal Medicine Fellowship Programs

Abstract: Objective To investigate the use of simulation in neonatal-perinatal medicine (NPM) fellowship programs. Study Design This was a cross-sectional survey of program directors (PDs) and simulation educators in Accreditation Council for Graduate Medical Education (ACGME)- accredited NPM fellowship programs. Results Responses were received from 59 PDs and 52 simulation educators, representing 60% of accredited programs. Of responding programs, 97% used simulation, which most commonly include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…Simulation-based training offers a safe risk-free environment for clinicians to develop and maintain competency [ 8 ]. Simulation-based training has become an integral part of many neonatal-perinatal medicine training programs, and is used as a basis for many standardized newborn training programs worldwide to teach neonatal procedures and resuscitation as noted in the 2021 European Resuscitation Council Guidelines [ 9 11 ]. In addition, simulation has the potential to play a key role in maintaining professional competency for infrequently performed high-risk procedures such as thoracentesis and extracorporeal membrane oxygenation (ECMO) [ 12 , 13 ].Simulation-based training is also a valuable tool in teaching behavioral skills such as effective communication, teamwork, and leadership, which are essential aspects of team performance.…”
Section: Simulation-based Training and Educationmentioning
confidence: 99%
“…Simulation-based training offers a safe risk-free environment for clinicians to develop and maintain competency [ 8 ]. Simulation-based training has become an integral part of many neonatal-perinatal medicine training programs, and is used as a basis for many standardized newborn training programs worldwide to teach neonatal procedures and resuscitation as noted in the 2021 European Resuscitation Council Guidelines [ 9 11 ]. In addition, simulation has the potential to play a key role in maintaining professional competency for infrequently performed high-risk procedures such as thoracentesis and extracorporeal membrane oxygenation (ECMO) [ 12 , 13 ].Simulation-based training is also a valuable tool in teaching behavioral skills such as effective communication, teamwork, and leadership, which are essential aspects of team performance.…”
Section: Simulation-based Training and Educationmentioning
confidence: 99%
“…A survey of perinatal and neonatal fellowship program directors showed that EC-D is a "very important" skill for fellows to learn 10 . Interestingly, the American Board of Pediatrics Content Outline for neonatal-perinatal medicine, which defines the body of knowledge…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A study done by Sawyer et al on simulation training in neonatal-perinatal medicine programs showed that about 97% of the programs offer simulation training to the fellows. Of note, most of the program directors felt that skills for EC-D are important or very important, but not mandatory for the fellows to learn 10 . Our study reinforces the need to incorporate EC-D in simulation training sessions for fellows.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…FA ZIT Neueste Expertenrichtlinien äußern sich daher sehr zurückhaltend bezüglich des Cord Milking [21]. [27]. Letztere Faktoren sind in geschulten Teams antizipierbar und zugänglich für spezifische Schulungen.…”
Section: Perinatale Kreislaufumstellung Und Atemumstellungunclassified